(3eaGJjM GdTQGFYs - (3GdcGTj Ch GdcGTGfj, eMSf Hf eQJVi Hf ajV Gddg eMehO, J (B1090(3g`s ((3eOjfI cGTGfs)
(3ChdgG (B:s
(3GdMeO ddg GdPj gOGfG dOjf GdESdGe(B...(3bGd ehdGfG(B...(3GdUGOb(B...(3GfXQhG Edi ef cGf efce Qhi MOjKfG hfXQ aj MdGdfG hMQGefG(B...(3aGQVhG Hg MceG(B...s
(3BNQgG (B:s
(3NdGaG gd JfaP ef GdCUd Ce GdKdK hjCJj GdcdGe ajg hSGFQ CMcGe GdhUGjG aj af GdYGOGJ hGdeYGedGJ Ef TGA Gddg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B5(3,U(B290s
(3EjVGM Gdecfhf(B:(3L(B2(3,U(B521s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis